2020
DOI: 10.1021/acschemneuro.0c00446
|View full text |Cite
|
Sign up to set email alerts
|

Brain and COVID-19 Crosstalk: Pathophysiological and Psychological Manifestations

Abstract: The world is experiencing one of the major viral outbreaks of this millennium, caused by a plus sense single-stranded RNA virus belonging to the Coronaviridae family, COVID-19, declared as pandemic by WHO. The clinical manifestations vary from asymptomatic to mild symptoms like fever, dry cough, and diarrhea, with further increase in severity leading to the development of acute respiratory distress syndrome. Though primary manifestations are respiratory and cardiac, various studies have shown the neuroinvasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 128 publications
0
9
0
2
Order By: Relevance
“…On October 7, 2020 searching on PubMed "COVID-19 OR COVID-2019 OR severe acute respiratory syndrome coronavirus 2 OR severe acute respiratory syndrome coronavirus 2 OR 2019-nCoV OR SARS-CoV-2 OR 2019nCoV OR (Wuhan AND coronavirus) AND brain" we found 1,293 papers and most of them showed that SARS-CoV-2 invades the CNS, developing neurological impairments such as stroke, epilepsy, anosmia and hypogeusia, seizures, and encephalitis (1,66,(233)(234)(235)(236). Specifically, a retrospective analysis by Mao et al (237) underlined that about 40% of SARS-CoV-2 patients developed headache, disturbed consciousness, and other brain dysfunction symptoms (1), and an autopsy study reported the presence of edema in brain tissue of SARS-CoV-2 patients (66).…”
Section: Brainmentioning
confidence: 99%
“…On October 7, 2020 searching on PubMed "COVID-19 OR COVID-2019 OR severe acute respiratory syndrome coronavirus 2 OR severe acute respiratory syndrome coronavirus 2 OR 2019-nCoV OR SARS-CoV-2 OR 2019nCoV OR (Wuhan AND coronavirus) AND brain" we found 1,293 papers and most of them showed that SARS-CoV-2 invades the CNS, developing neurological impairments such as stroke, epilepsy, anosmia and hypogeusia, seizures, and encephalitis (1,66,(233)(234)(235)(236). Specifically, a retrospective analysis by Mao et al (237) underlined that about 40% of SARS-CoV-2 patients developed headache, disturbed consciousness, and other brain dysfunction symptoms (1), and an autopsy study reported the presence of edema in brain tissue of SARS-CoV-2 patients (66).…”
Section: Brainmentioning
confidence: 99%
“…Social and family contacts have been reduced (14), there are fewer work opportunities and salaries have dropped (15), access to healthcare facilities has been hampered (16,17), and our future financial well-being and health along with that of our families is uncertain (18). All these factors may be having a negative impact on our psychological equilibrium (19,24), and this could be particularly evident in menopausal women, who are already living a critical period of their lives (5,17,22,23). In these women, the COVID-19 pandemic may change the prevalence of symptoms and the composite picture of menopausal complaints.…”
Section: Introductionmentioning
confidence: 99%
“…More than a third of patients with COVID-19, especially those with severe to critical COVID-19 who managed on an intensive care unit (ICU) develop central nervous system (CNS) symptoms and signs (e.g., headache, dizziness, ataxia, seizure, delirium, confusion, impaired consciousness) consistent with CNS involvement and /or neurological complications (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebrovascular complications of viral sepsis, including ischemic or hemorrhagic stroke, CNS involvement in CRS, hypoxia as well as the interplay of comorbidities have been implicated as contributing factors (6)(7)(8)(9)(10)(11)(12)(13). Due to the neuro-invasive capability of SARS-CoV-2, acute disseminated encephalomyelitis (ADEM) and viral encephalitis have also been suspected in some patients (13).…”
Section: Introductionmentioning
confidence: 99%